METHODS FOR DETERMINING THE ACUTE POISONING AND CUMULATIVE PROPERTIES OF A NATURAL REMEDY “AS-SULTAN” (Scientific journal of the Fergana State University, 2025)
Based on local plants a new biologically active food additive developed As-Sultan – a natural food supplement that replaces certain synthetic drugs that help prevent and treat gallbladder inflammation acute toxicity and Preclinical tests were conducted to determine the cumulative properties. According to the results of the experiments, it was determined that the average lethal dose of the As-Sultan food additive is LD50>10000 mg/kg. The chemical compounds were classified as belonging to the relatively harmless VI class of acute toxicity. It was proven that they do not have a cumulative property.